2022
DOI: 10.1186/s13046-022-02271-y
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer development is affected by the ECM molecule EMILIN-2 hinging on macrophage polarization via the TLR-4/MyD88 pathway

Abstract: Background Colorectal cancer is one of the most frequent and deadly tumors. Among the key regulators of CRC growth and progression, the microenvironment has emerged as a crucial player and as a possible route for the development of new therapeutic opportunities. More specifically, the extracellular matrix acts directly on cancer cells and indirectly affecting the behavior of stromal and inflammatory cells, as well as the bioavailability of growth factors. Among the ECM molecules, EMILIN-2 is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 99 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…They may also secrete immunosuppressive molecules, aiding tumors in evading immune surveillance ( Batalha et al, 2023 ; Gawinski et al, 2023 ). Conversely, some monocytes can differentiate into immunologically active cells like M1-type macrophages and certain dendritic cells, enhancing the immune response against tumor cells ( Andreuzzi et al, 2022 ; Ito et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…They may also secrete immunosuppressive molecules, aiding tumors in evading immune surveillance ( Batalha et al, 2023 ; Gawinski et al, 2023 ). Conversely, some monocytes can differentiate into immunologically active cells like M1-type macrophages and certain dendritic cells, enhancing the immune response against tumor cells ( Andreuzzi et al, 2022 ; Ito et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that TLR4 activation can promote the polarization of macrophages towards the M1 phenotype via the TLR-4/MyD88/NF-κB pathway. 368 Furthermore, in a mouse model of peritoneal carcinomatosis of colorectal cancer, a high-fat diet was found to promote M1 polarization of adipose tissue macrophages (ATMs) by activating TLR4. The intrinsic knockout of TLR4 in macrophages significantly reduced the expression of TNFα, IL-1β, and CXCL10 induced by a high-fat diet.…”
Section: Innate Immune Pathways In Cancermentioning
confidence: 99%
“…In a study on colorectal cancer, EMILIN-2 was found to promote M1 polarization through activation of the TLR-4/myeloid differentiation factor-88/NF-κB signaling pathway. EMILIN-2 deficiency is associated with increased M2 macrophage infiltration ( 39 ). This suggests that certain components of the ECM are key regulators of the tumor-associated inflammatory environment and may represent promising prognostic biomarkers for tumor patients.…”
Section: Polarization Of Macrophagesmentioning
confidence: 99%